Effect of Turny Flour Supplementation on Egg Weight and the Color of Yellow Egg (Yolk) Layer Niaga Chicken: Pengaruh Suplementasi Tepung Kunyit Terhadap Bobot Telur dan Warna Kuning Telur (Yolk) Ayam Niaga Petelur - Anggun Marisa; Sigit Mugiyono; Ibnu Hari Sulistyawan; Kususiyah Kususiyah (BPFP Universitas Bengkulu, 2026)
The research materials consisted of 80 commercial laying hens maintained for 8 weeks. The hens were kept in battery cages, each containing four birds, equipped with feeders and drinkers, as well as tools for measuring egg quality. The feed used during the production period consisted of ground corn (50%), rice bran (25%), and concentrate (25%) with nutrient content of 2900 kcal/kg metabolizable energy, 17.5% crude protein, 3% calcium (Ca), and 1.6% phosphorus (P). This study employed an experimental method by measuring egg weight and yolk color with the addition of turmeric powder supplementation. The experimental design used was a Completely Randomized Design (CRD) with four treatments and five replications. The treatments were: P0 (control), P1 (1% turmeric powder), P2 (2% turmeric powder), and P3 (3% turmeric powder). The results of analysis of variance showed that the addition of turmeric powder had no significant effect (P > 0.05) on egg weight, but had a highly significant effect (P < 0.01) on yolk color. It can be concluded that supplementation of 2–3% turmeric powder improves yolk color, with the highest yolk color observed in P3 (3% turmeric powder).